Métodos clínicos fonoaudiológicos utilizados no atendimento de pacientes com transtorno global do desenvolvimento: revisão sistemática de literatura - Ferreira, Danielle Miranda (2013)
Introduction: The Global Developmental Disorders (GDD) are characterized by impaired social interaction, by stereotyped and repetitive use of language and the presence of repetitive behaviors with restricted interests (BOSA C, Gomes VF, 2004), and has indicated speech therapy treatment. Objective: Analyze the scientific literature on clinical speech therapy methods used in GDD patients treatments from systematic literature review. Methods: Systematic review of literature from exploratory character. Secondary study subsidized by previous realized studies. 46 articles were selected, published between 2000 and 2011 using search strategy in databases EMBASE, LILACS, PUBMED and SciELO, and categorized according to the proposed therapies for the treatment of GDD and their levels. Results: From the 46 selected articles, there was predictable diversity of proposals regarding the analyzed variables. From the results it can be concluded that there are several proposals for the speech therapy of GDD; associated with epistemological, methodological and cultural diversity that characterizes the study theme approach, nationally and internationally. The selected studies had low levels of evidence, as the patients were mostly children, demonstrating a concern for early intervention, the therapy length ranged, but mostly of them were realized around 6 months to 1 year. The systematic review showed itself the method that can contribute to the speech therapy, despite the difficulties founded on this and other studies. Conclusion: Regardless of the therapeutic approach used to treat the GDD, it is important to recognize that, in most of analyzed publications, the researchers report the clinical evolution of these patients, proving the importance of speech therapy, individual or multidisciplinary